An investigation of the Severity levels of Loneliness suicidal ideation among Patients with Major Depressive Disorder in Sulaimani City/Iraq Kurdistan - Abdulkarim, Araz Mohammed; Muhsin, Salwa Shakir (Sulaimani Journal for Pure and Applied Sciences, 2021)
Background: Major depressive disorder has become one of the most common mental disorders worldwide. Loneliness considers significant psychological distress associated with depression and suicidality. It is important to be detected and interviewed for patient safety. Aim: This study aims to find the prevalence rates the severity levels of loneliness and to identify risk factors among community-based patients with major depressive disorder. Methods: A total of 250 patients with major depressive disorder were recruited from a psychiatric clinic in Ali Kamal Consolation Centre in Sulaimani city included in this cross-sectional study. The data were collected from September 2020 to March 2021 through the utilization of interviews guided by the items of the questionnaire. The ULLA loneliness scale, Beck suicide ideation inventory, Beck depression inventory, sociodemographic, and psychiatric history characteristics were included in the questionnaire. The SPSS version 25 was used for data analysis. Results: All the studied patients with major depressive disorder mean age ± SD was 38.7 ± 12.4 years, 60% of females had a feeling of loneliness. The most significant proportion of the patients had (62.8%) a frequent level of loneliness, with 43.2% mild form of depression and 64.4% had a moderate level of suicidal ideation. It is evident in this study that more than half (51.5%) of patients with suicidal attempts had a feeling of loneliness, which was significantly higher than the rate (27.8%) among those with no history of suicidal attempt (p < 0.0.1). Conclusion: Suicidal Patients with major depressive disorder had experience feelings of loneliness at a frequent level. The severe level of loneliness was a predictor of the severity level of depression and suicidal ideation. Recommendation: Regular evaluation of loneliness and depression can help to detect patients at risk of suicidal behavior and encourage greater social engagement in daily life activities for patients with depression.
Keywords: Loneliness; Major depressive disorder; the Severity level